A focus on riociguat in the treatment of pulmonary arterial hypertension. Issue 3 (4th July 2019) - Toxvig, Anne Kathrine; Wehland, Markus; Grimm, Daniela; Infanger, Manfred; Krüger, Marcus
Abstract: Current treatment of pulmonary arterial hypertension (PAH) targets three signalling pathways: the nitric oxide (NO) pathway, the endothelin pathway and the prostacyclin pathway. Riociguat is a soluble guanylate cyclase stimulator, acting via the NO pathway in a new way: unlike other common drugs targeting this pathway (eg tadalafil and sildenafil), riociguat acts independently of endogenous NO. This MiniReview focuses on PAH treatment with riociguat and on its advantages and disadvantages compared with other drugs targeting the NO pathway. In the PATENT‐1 trial (NCT00810693), riociguat improved significantly the 6‐minute walking distance in patients suffering from PAH, with a mean difference (MD) of 36 m compared with a placebo group. The results are comparable to those found for its competitors tadalafil (MD of 33 m) and sildenafil (MD of 50 m) in the PHIRST‐1 trial ( NCT00125918) and the SUPER‐1 trial (NCT00644605). No obvious advantages were found regarding pharmacokinetic features and adverse events. In the RESPITE study (NCT02007629), patients with PAH with insufficient response to treatment with tadalafil or sildenafil were switched to riociguat. These results indicate that riociguat might be superior regarding efficacy to PDE‐5 inhibitors in a patient group, where endogenous NO production might be insufficient. This finding was further examined in the REPLACE study (NCT02891850). Moreover, riociguat has shown promising anti‐proliferative, anti‐inflammatory and anti‐fibrotic effects in animal models. Further investigations are needed to determine whether this applies also to human beings. Taken together, riociguat induces vasodilation of the pulmonary arteries and leads to an improvement in the ability to carry out physical activity.